THE EFFECT OF SERVICE QUALITY AND PRODUCT QUALITY ON PURCHASE DECISIONS AT THE MERY COYONG STORE IN MANGGA DUA - Lisna Sintiana Pasaribu; Nur Nia Ramadany; Syari’ah Az-Zahra (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to determine the influence of service quality and product quality on purchase decisions at Mery Coyong Store Mangga Dua, both partially and simultaneously. The research method used was quantitative with a simple random sampling technique, as many as 40 respondents who were active consumers of Mery Coyong Store. Data was collected through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that all research instruments were valid and reliable (Cronbach's Alpha 0.980 and 0.942). The results of the t-test showed that the quality of service had no significant effect on the purchase decision (Sig. 0.287 > 0.05), while the quality of the product had a positive and significant effect (Sig. 0.000 < 0.05). The regression analysis yielded the equation Y = 7.081 + 0.149X1 + 0.433X2. Simultaneously, service quality and product quality had a positive and significant effect on purchase decisions (F count 45.317; Sig.<0.001), with a contribution of 71.0% (R²=0.710), while the remaining 29.0% were influenced by other factors outside the study.